Respective Advantages of Growing Different Green Manure With Nitrogen Fertilization in Cotton‐Based Cropping Systems: Insights From a Three‐Year Field Study - Zhenggui Zhang; Jian Wang; Weibin Huang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Shiwu Xiong; Minghua Xin; Yabing Li; Zhanbiao Wang (Food and Energy Security)
ABSTRACT Planting green manure to improve cash crop yield and soil health has been widely recognized, and understanding cash crop performance after green manure integration is pivotal for determining its potential to bolster and enhance crop productivity and sustainable production. However, it is unclear whether the effects of different types of green manure on subsequent cash crops are uniform. In order to clarify this issue, we systematically analyzed the effects of green manure types and nitrogen (N) application rates on succeeding cotton agronomic performance, yield, biomass, yield stability, and nutrient uptake. A split‐plot experiment with two factors was designed, main factor includes four cover cropping systems monoculture cotton (MC), February orchid/cotton cover cropping (FoC), hairy vetch/cotton cover cropping (HvC), and a mixture of February orchid and hairy vetch/cotton cover cropping (FHC), and sub‐main factor include four N application levels (0 (N0), 112.5 (N1), 168.75 (N2), and 225 (N3) kg N ha−1). Results suggests that nonlegume green manure (February orchid) accumulated more biomass, N, P, and K nutrients than the legume green manure (hairy vetch) and green manure mixture. Compared with cotton yield of MC, the FoC, HvC, and FHC system increased by 5.8%, 7.6%, and 15%, respectively. N use efficiency was more significantly influenced by the N application rates than by cropping systems. Specifically, as N application rates increased, N use efficiency decreased under MC, HvC, and FHC systems, while it increased under the FoC system. Additionally, we observed a trade‐off between cotton yield and yield stability, with the highest yield stability when cotton yield reached 2633 kg ha−1. This study provides evidence that nonlegume green manure (February orchid) with greater advantages on cotton vegetative organ growth, legume green manure (hairy vetch) can promote nutrient uptake compared to other green manure, while green manure mixture (February orchid and hairy vetch mixture) significantly increased cotton yield and yield stability. These findings provide evidence‐based insights highlighting the respective benefits of incorporating diverse species of green manure into cotton‐based cropping systems in the Yellow River Basin of China.